Complete mitochondrial genome of endangered Arabian tahr (Arabitragus jayakari) and phylogenetic placement. Issue 6 (3rd June 2022) - Al-Rawahi, Ahmed N.; Alalawi, Zahir S.; Asaf, Sajjad; Khan, Abdul Latif; Khan, Adil; Al-Rawahi, Haitham; Ross, Steven; Al-Jahdhami, Mansoor; Al-Harrasi, Ahmed
Abstract: The Arabian tahr ( Arabitragus jayakari ) endemic to mountains of northern Oman and the United Arab Emirates, however, the species is faced with significant threats to its population. Because of its small and dwindling population, it is listed as Endangered. Here, we sequenced and assembled the mitochondrial (mt) genome of A. jayakari into 16, 485 bp with 39.6% GC content. It also contains 13 protein-coding genes, 22 tRNA genes, and two rRNA genes. Phylogenetic analysis of A. jayakari with related 12 species mt genomes showed that A. jayakari forms a monophyletic clade with Hemitragus jayakri . In the current context of a changing environment, evolutionary analysis based on mitochondrial genome will aid in identifying evolutionary changes among different species and analyzing shared gene pools to counteract threats.